Comparison Of Polygamy Laws Between Indonesia, Egypt And Kenya - Maswandi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Polygamy is a marriage in which one of the parties having or marrying someone of the opposite sex simultaneously. Experts distinguish the term for a man who have more than one wife with the term polygyny and for a women who have more than one husband use the term polyandry. Therefore, a marriage performed by a man who have more than one wife at the same time called polygyny is not polygamy. Polygamy in Indonesia is regulated in the Marriage Act 1974, KHI and Government Regulation No. 9 of 1975 on the implementation of the law Article 9/1975), for the country of kenya mentioned in Article 49 paragraph 3 of the Kenya Marriage Act of 2014 as well as the law EgyptArticle 11 of Bis law No. 25 of 1929 as amended by law No. 100 of 1985. The research method used is normative legal research with a statute legal approach and a conceptual approach. Results: Indonesia allows polygamy with the permission of the wife and the Religious Court as a form of legal order with maximum limit of four wives, in accordance with the rules contained in the act marriage law and KHI. The Marriage Act of Kenya allow polygamy with the provisions included in the marriage potentially polygamous or polygamous as well as only require voluntary between men and women who will marry without setting limits on the number maximum in polygamy while enurut law Egypt Article 11 Bis of Law No.25 of 1929 as amended by Law No.100 of 1985 husband he must inform his first wife in court of the want to do a second marriage